Validation of the Korean version of the Moral Judgment Scale: A process dissociation approach to moral dilemmas - Jang, Eunyoung (Heliyon, 2020)
Conway and Gawronski proposed a scale that independently measures utilitarian and deontological inclinations underlying moral judgments, based on an individual's endorsement of acceptable or unacceptable responses to 10 congruent and 10 incongruent moral dilemmas. This study aimed to develop and standardize the Korean version of this scale and examine the psychometric characteristics of various indexes extracted from it. The English version was translated and back-translated by two independent bilinguals. Inconsistencies between the backward translated version and the original version were resolved by consultation with an independent psychologist. Using an online survey, Korean adults aged 18 years or older were asked to read 20 dilemmas in the Korean version and indicate whether the action undertaken in each dilemma was acceptable, the probability that they would undertake the action themselves, and their level of tension and happiness. A total of 469 adults participated. Participants additionally answered questions that assessed utilitarianism and their level of antisocial personality disorder. Analysis showed that it was appropriate to use 20 dilemmas (10 incongruent and 10 congruent) in Korean adults but psychometric characteristics were different from those of the original English version. The correlation of probability that utilitarianism would drive responses (KU) and the probability that deontology would drive the responses (KD) was -.23 (p < .001). KU showed a significant correlation with utilitarianism (.18, p < .001) and a near-zero correlation with antisocial personality disorder. KD showed a correlation of -.27 (p < .001) with utilitarianism and a correlation of -.13 (p < .01) with antisocial personality disorder. A previous study that proposed that utilitarian and deontological inclinations are independent in moral judgment found a near-zero correlation between U and D, which was different from the result of the present study. Additionally, the limitations and implications of this study are discussed.